Making it in China: The determinants of economic success in a socialist market system - Ion Marandici (Socialism, Capitalism and Alternatives: Area Studies and Global Theories, 2019)
China's politicians like to emphasise that they are building a socialist market economy based on the ideology of socialism with Chinese characteristics. Unlike other post-communist transitions to capitalism, China's radical economic transformations during the neo-liberal era did not generate a large pool of economic losers. On the contrary, over the last three decades, seven hundred million Chinese escaped poverty. Yet at the same time, China's impressive economic growth has been associated with the rise of a wealthy elite, which gradually is being co-opted by the party-state. Relying on elite-level and survey data, this study goes beyond socio-demographic characteristics and investigates whether party membership, education, beliefs in upward mobility and support for an interventionist state correlate with income levels. The final section discusses the implications of the observed trends for the future of the Chinese economic model.
Keywords: P3; P16; P5; P30; 330; China; political economy; wealthy elites; superrich; income; communism